2010
DOI: 10.5433/1679-0359.2010v31n2p321
|View full text |Cite
|
Sign up to set email alerts
|

Novos compostos de milho-pipoca para o Brasil

Abstract: ResumoApesar dos avanços, o número de variedades e híbridos comerciais de linhagens de milho-pipoca é reduzido. Assim, o objetivo deste trabalho foi avaliar novos compostos desenvolvidos no Brasil e indicar os de maior potencial genético para iniciar um trabalho de melhoramento intrapopulacional. A pesquisa foi desenvolvida no ano agrícola 2005/2006. Os tratamentos constaram de 21 genótipos (híbridos de linhagens, compostos e sintéticos) cultivados em dois municípios, Umuarama e Cidade Gaúcha, ambos no Noroest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
0
10
1
5
Order By: Relevance
“…Therefore, in comparison with the controls, which are commercial hybrids prominent in the Brazilian market, the populations used in this study have high productive potential. Matta and Viana (2003), Scapim et al (2010), and Vieira et al (2009) used the hybrid IAC-112 and/or IAC-125 as the controls (consistent with those used in the present study) and observed superiority of these hybrids in their studies; however, these hybrids were not superior to the different selection cycles of the present study, which confirms the productive potential of the populations.…”
Section: Resultscontrasting
confidence: 46%
“…Therefore, in comparison with the controls, which are commercial hybrids prominent in the Brazilian market, the populations used in this study have high productive potential. Matta and Viana (2003), Scapim et al (2010), and Vieira et al (2009) used the hybrid IAC-112 and/or IAC-125 as the controls (consistent with those used in the present study) and observed superiority of these hybrids in their studies; however, these hybrids were not superior to the different selection cycles of the present study, which confirms the productive potential of the populations.…”
Section: Resultscontrasting
confidence: 46%
“…Popcorn breeding programs in Brazil have emerged with the use of intra and interpopulational recurrent selection to increase productivity and popping expansion (Daros et al 2004;Faria et al 2008;Freitas Júnior et al 2009;Amaral Júnior et al 2010); composite obtainment (Rangel et al 2008;Vieira et al 2009a;Scapim et al 2010); evaluation and introduction of disease resistance in commercial materials (Miranda et al 2002;Vieira et al 2009b); evaluation of the genetic diversity for agronomical traits and molecular markers (Dandolini et al 2008;Miranda et al 2008;Munhoz et al 2009;Leal et al 2010;Trindade et al 2010); use of in vitro culture (Ricci et al 2007;Fernandes et al 2008); hybrids obtainment and its evaluation (Vieira et al 2009c;Vieira et al 2009a;Silva et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…A capacidade de expansão também apresentou valores aceitáveis para a experimentação agrícola (respectivamente, 12,5% e 13,8%), quando comparada com outros autores (DAROS; AMARAL JÚNIOR; PEREIRA, 2004;FREITAS JÚNIOR et al, 2006;RANGEL et al, 2007;SCAPIM et al, 2010;MILANI, 2011 : heterose do cruzamento da i-ésima família S 2 com o testador 'j'; do teste F. Quando necessário, as médias obtidas foram ajustadas, levando-se em consideração a recuperação da informação interblocos. Por meio das médias dos tratamentos ajustados foi realizada a análise em dialelo parcial, utilizando o modelo proposto por Griffing (1956), adaptado por Geraldi e Miranda Filho (1988) aos cruzamentos dialélicos parciais, em que foram avaliadas pq combinações híbridas sendo p famílias S 2 (Grupo I) e q testadores (Grupo II).…”
Section: Resultsunclassified
“…A capacidade de expansão também apresentou valores aceitáveis para a experimentação agrícola (respectivamente, 12,5% e 13,8%), quando comparada com outros autores (DAROS; AMARAL JÚNIOR; PEREIRA, 2004;FREITAS JÚNIOR et al, 2006;RANGEL et al, 2007;SCAPIM et al, 2010;MILANI, 2011 …”
Section: Resultsunclassified